2004
DOI: 10.1593/neo.04214
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of a Fibroblast Growth Factor-Binding Protein during Skin Carcinogenesis and Wound Healing

Abstract: The initiation of premalignant lesions is associated with subtle cellular and gene expression changes. Here we describe a severe combined immunodeficiency mouse xenograft model with human adult skin and compare chemical carcinogenesis and wound healing. We focus on a secreted binding protein for fibroblast growth factors (FGF-BP) that enhances the activity of locally stored FGFs and is expressed at high levels in human epithelial cancers. Carcinogen treatment of murine skin induced papilloma within 6 weeks, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…16,21 and expression was found downregulated after the neonatal period. Consistent with a role in cancer, FGF-BP expression was found to be induced early during malignant transformation of mouse and human skin 16,22 and colon epithelia, 23 as well as upregulated in squamous cell carcinomas and colon cancers relative to normal tissues. 14,15,20,23 Transient upregulation of FGF-BP was found during wound healing of mouse and human skin.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…16,21 and expression was found downregulated after the neonatal period. Consistent with a role in cancer, FGF-BP expression was found to be induced early during malignant transformation of mouse and human skin 16,22 and colon epithelia, 23 as well as upregulated in squamous cell carcinomas and colon cancers relative to normal tissues. 14,15,20,23 Transient upregulation of FGF-BP was found during wound healing of mouse and human skin.…”
mentioning
confidence: 57%
“…14,15,20,23 Transient upregulation of FGF-BP was found during wound healing of mouse and human skin. 22 On the other hand, retinoids were found to rapidly reduce expression of FGF-BP by transcriptional repression and reduction of mRNA stability in cultured tumor cells 24,25 and in normal tissues and xenograft tumors in intact animals. 26,27 Recombinant human FGF-BP enhances FGF-dependent angiogenesis, 17 expression of FGF-BP in nontumorigenic cells can induce the formation of angiogenic tumors 14 and depletion of FGF-BP from human colon cancer or squamous cell carcinoma cells by ribozyme-targeting showed a rate-limiting role for tumor growth and angiogenesis.…”
mentioning
confidence: 99%
“…FGF-BP can release the immobilized FGFs (for example, bFGF) from the extracellular matrix and chaperone them to their receptors. FGF-BP has been suggested to be important in several physiological and pathological processes including epithelial development, wound healing and tumorigenesis (Kurtz et al, 1997(Kurtz et al, , 2004Aigner et al, 2001). FGF-BP is lowly expressed in normal adult human tissues and upregulated in several tumor types including invasive breast cancer (Kagan et al, 2003), prostate cancer, squamous cell carcinoma (Li and Chen, 2004) and colon cancer (Ray et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, exogenously added FGF-BP1 enhances keratinocyte migration. 16 Together with the finding that expression levels of the fgfbp1 transgene were particularly high in keratinocytes of the epidermis and the hair follicles, 6 this finding indicates that re-epithelialization may also be accelerated in the FGF-BP1 transgenic mice. Indeed, the accelerated wound closure that was observed in these animals supports this hypothesis, although it remains to be determined whether this resulted from enhanced contraction and/or from enhanced re-epithelialization.…”
Section: Fgf-bp1 Enhances Angiogenesis Fibroblast Migration and Woumentioning
confidence: 85%
“…16 In another study, enhanced expression of FGF-BP1 was shown throughout the healing process of full-thickness excisional skin wounds in mice, and particularly strong expression of FGF-BP1 was observed in the hyperproliferative wound epidermis. 17 In vitro studies with cultured keratinocytes suggested that various growth factors that are abundant at the wound site are responsible for the increase in FGF-BP expression in the wound epidermis.…”
Section: Expression Of Fgf-bp1 In Healing Skin Woundsmentioning
confidence: 95%